Nonlinear region of attraction analysis for hypersonic flight vehicles' flight control verification. (8th May 2017) - Chen, Jie; Ma, Cun Bao; Song, Dong
The stability analysis method based on region of attraction is proposed for the hypersonic flight vehicles' flight control verification in this article. Current practice for hypersonic flight vehicles' flight control verification is largely dependent on linear theoretical analysis and nonlinear simulation research. This problem can be improved by the nonlinear stability analysis of flight control system. Firstly, the hypersonic flight vehicles' flight dynamic model is simplified and fitted by polynomial equation. And then the region of attraction estimation method based on V – s iteration is presented to complete the stability analysis. Finally, with the controller law, the closed-loop system stability is analyzed to verify the effectiveness of the proposed method.